Semi-circular potential sweep voltammetry: experimental verification and determination of the formal potential of a reversible redox couple - Amin, H; Uchida, Y; Kätelhön, E; Compton, R (Elsevier, 2019)
The use and merits of a semi-circular potential waveform in place of the conventional triangular waveform has been reported [J. Electroanal. Chem. 2018, 818, 140–148] on the basis of computational simulations. We report the experimental application of this new method to the study of the electrochemically reversible [Ru(NH3)6]3+/2+ redox couple at a macroelectrode. The method is used to determine the formal potential of this redox couple. Agreement between theory and experiment is good.